Experience on clinical simulation in physiotherapy students - Santos Lucio Chero Pisfil; Aimeé Yajaira Díaz Mau; Milagros Nohely Rosas Sudario; Pierre Alberto Huamani Escudero; Jhosely Quispe Nina; Rosmy Gagliuffi Artica (Medisur)
Foundation: clinical simulation in health integrates into practice, the skills learned from theory. It is a learning resource to improve what has been learned that minimizes the risk to patients. Objective: to describe the experience achieved on simulation by physiotherapy students. Methods: descriptive study developed at the Norbert Wiener University with VIII cycle students of the cardiorespiratory physiotherapy course. A skills workshop was developed and subsequently a clinical simulation scenario with a standardized patient with decompensated chronic respiratory disease. Two satisfaction questionnaires were applied at the end of each experience carried out. Results: 102 students participated in the skills workshop, the average age was 26.71 ±6.45; female 82.35%. A seven-question satisfaction questionnaire was applied, which reflected 90% acceptance, Cronbach's alpha of 0.796. 93 students participated in the simulation scenario, age 28.65 ±5.83, female 81.6%, work and study 65.51%, a 13-question questionnaire that measured five dimensions, acceptance of 88.7%. , consistent and reliable Cronbach's alpha of 0.913. Conclusions: a new scenario was used that ensures competencies in the clinical field based on simulation for the training of physiotherapy students, with good acceptance of the experience carried out.